Cell phone contamination among students and faculty members of the faculty of dentistry of Isfahan university of medical sciences - Firoozeh Nilchian; Faezeh Falahati; Tahmineh Narimani (Tehran University of Medical Sciences, 2018)
Background and Aims: The cell phone has played a significant role in the transmission of microbial contamination as a public tool. The present study was conducted to determine the degree of contamination of mobile phones of students and staff of the dental school of Isfahan University of Medical Sciences. Materials and Methods: In a cross-sectional study, 60 samples were taken from 60 cell phones belonging to students, staff and faculty members of the Isfahan Dental School, the samples were cultured in the laboratory for microbial contamination of the phone. The behavioral characteristics of the subjects were also determined using a cell phone special questionnaire. Data were analyzed by SPSS version 24 using descriptive statistics, one-way AVONA, T-test and Chi square. Results: Among the 60 cultured samples, 11 (18.3%) did not grow any bacteria. In 31 cases (51.7%), Staphylococcus epidermidis, 14 cases (23.3%) Staphylococcus aureus susceptible to methicillin and in 4 (6.7%) methicillin resistant staphylococcus aurous were grown. The mean of bacteria colonization was 18±12.2 and there was not any relation between the colonization and kind of bacteria (P=0.78) and studied groups (P=0.43). Also, there was a significant difference between the sanitary conditions and the type of bacteria grown in the culture medium (P=0.04). Conclusion: According to the results of the study, the cell phones belonging to the students, lecturers and faculty staff were contaminated by harmful bacteria such as staph aurous. These bacteria are the most important of nosocomial infections and may be led to a wide areas of infections from simple to serious types.